Energy potential of residual biomass from agro-industry in a Mediterranean region of southern Italy (Campania). (20th December 2020) - Di Fraia, Simona; Fabozzi, Salvatore; Macaluso, Adriano; Vanoli, Laura
Abstract: According to the Italian national Energy strategy elaborated in 2017, the biomass sector has one of the most important strategic roles in energy renewables policy. Thus, estimating the potential of this resource is crucial for its energy valorization. Therefore, in this paper, a method to assess the energy potential from residual biomass is presented. The availability of residual biomass and its energy potential are estimated by using statistical and literature data. To account for the variability of the factors taken into account a comprehensive literature review is carried out focusing on the case studies related to Mediterranean areas. Based on the collected data, uncertainty analysis and sensitivity analysis are performed to provide reliable results. As a case study, the energy potential of residual biomass from agro-industry in the Campania region (southern Italy) is considered. The proposed method allows estimating a total of about 14.5 PJ per year of recoverable primary energy potential in the Campania region, which may cover around 14% of its thermal demand. The analysis carried out is intended to be a useful tool for policymakers of Mediterranean regions, to integrate energy recovery from agro-industrial biomass in the regulatory and investment strategies of the energy sector. Highlights: A model to estimate energy potential of residual biomasses typical of Mediterranean climate conditions is presented. As a case study, a southern Italy region is taken into account. The recoverable bio-energy potential may cover around 16% of the regional thermal demand. The analysis may be a useful tool for policymakers of Mediterranean regions.